BREAST CANCER SCREENING. - PhD Orifjon Absamatillayevich Talipov (Western European Studies, 2025)
Breast cancer is one of the most prevalent cancers among women worldwide. Early detection through regular screening significantly improves survival rates and reduces mortality. Common screening methods include mammography, clinical breast examination, and breast self-examination. This article reviews current guidelines, effectiveness, and challenges of breast cancer screening programs, emphasizing the importance of timely diagnosis and patient education.
Keywords: Breast cancer; screening; early detection; mammography